Impact of Problem-Focused and Emotion-Focused Coping Strategies on Psychological Well-Being among Vocational High School Teachers in Remote Teaching Settings - Yulinda, Rita; Na’imah, Tri; Wulandari, Dyah Astorini; Herdian, Herdian (Universitas Pakuan, 2024)
This study investigates the influence of problem-focused coping and emotional-focused coping on the psychological well-being of teachers during the pandemic. The pandemic created new stressors for teachers who were required to rapidly adapt to online learning technologies while maintaining the quality of instruction and student engagement. Using a quantitative correlational design, the study involved 119 teachers from Muhammadiyah Vocational High Schools (SMK) in Banyumas Regency, selected through simple random sampling from a population of 217 teachers. Three validated instruments were used: the Psychological Well-Being Scale (α = 0.873), Problem-Focused Coping Scale (α = 0.908), and Emotional-Focused Coping Scale (α = 0.865). Data were analyzed using multiple linear regression. The results revealed that both problem-focused coping (t = 6.789, p 0.05) and emotional-focused coping (t = 8.964, p 0.05) significantly affected psychological well-being. Simultaneous analysis also confirmed a significant combined influence of the two coping strategies (F = 50.889, p 0.05) with an adjusted R² of 0.458, indicating that 45.8% of the variance in psychological well-being was explained by coping mechanisms. The findings suggest that teachers who apply effective problem-solving strategies and emotional regulation are more capable of maintaining positive mental states, reducing stress, and achieving psychological resilience in their professional duties. The study highlights the importance of fostering adaptive coping strategies through training and institutional support to enhance teachers’ mental health and overall performance in challenging educational contexts.